Förbättrad slutredovisning efter utförd avverkning - Persson, Johan (2017)
The report Improved final accounting is produced in cooperation with Holmen Skog. The thesis comprises 15 credits at C level in the subject forest management. With a holding of 1.3 million hectares Holmen Skog is one of the largest actors on the Swedish timber market. Besides felling in own forest holdings, Holmen Skog acquires about 11.4 million (2014) m3 wood from external sources. The large amount of external purchase of wood inevitably results in large amount of transactions that should be presented, what was the outcome from the final felling/thinning? Both economical and per square meter/assortments is supposed to be presented. The origin of this study comes from Holmen Skog´s striving to increase their wood supplier’s total satisfaction and experience after the finished deal. Final accounting after finished final felling and thinning has for a long time been an area with a great deal of opinions from both forest owners and Holmen employees. The purpose of this report is to clarify if there are any problems with the final accounting and if so, what can be done better or different. Through two surveys, one to forest owners and one to Holmen employees information was collected and complied. The frequency of response among forest owners was about 31 percent and within Holmen employees about 71 percent. In total this is equivalent to almost 500 unique answers. The results show that there are several areas where improvements are possible, for example the presentation of volumes, incomes and costs. Many voluble comments emerged that should be taken seriously in the upcoming process with developing a new and improved layout for the final accounting.